Hepatitis C virus recurrence and immunosuppression-free state after liver transplantation. (September 2012) - Manzia, Tommaso Maria; Angelico, Roberta; Toti, Luca; Lai, Quirino; Ciano, Paolo; Angelico, Mario; Tisone, Giuseppe
HCV-related disease is the most common indication for liver transplantation (LT). HCV recurrence, which is almost universal, has a significant impact on patient and graft survival after LT and still represents a great unsolved issue for the liver transplant community. Several treatment strategies have been proposed. Since antiviral therapy has limited efficacy and can be administrated only in selected transplant recipients and additionally that immunosuppressive drugs have a negative impact on HCV re-infection, the achievement of an immunosuppression-free state after LT could play a central role in the avoidance of rapid HCV recurrence.